A decade of editing the European economic review - Zvi Eckstein; Esther Gal-Or; Thorvaldur Gylfason; Jürgen von Hagen; Gerard A. Pfann (Institute for the Study of Labor (IZA), 2011)
This story describes the circumstances that led to all five of us starting as editors at the same time, the unexpected things we have found, the unanticipated reactions we have encountered, how we worked as an editorial team, the central role of the editorial office manager, how we managed to work with five different publishers in ten years, the various initiatives we have developed to involve associate editors and referees, the early electronic editing system, and the creation of the essential database of potential referees. We will also describe the difficulties we have encountered in reaching one of our early goals to reduce the median time of first response to less than four months. Along the way, we will share a few anecdotes to illustrate the work of an academic journal editor.
urn:nbn:de:101:1-201110102585
Keywords: A11; A14; 330; journal; editing; economics; Wirtschaftswissenschaft; Fachzeitschrift; Europa